Salutogenesis: the case for a holistic tool for paramedic assessment of wellness. (2nd October 2019) - Cockrell, Krista; Reed, Buck; Agarwal, Gina; Wilson, Leigh
Abstract : Sense of coherence (SOC), the capacity to muster, believe in and value resources to support resilience, is a central component of the salutogenic approach to wellness. Assessing patients' SOC in a salutogenic model may be useful to paramedics as an adjunct to effective referral to care pathways other than via the emergency department and for predicting patient engagement. A tool to help direct practitioners in the prehospital environment towards the most appropriate resources for each patient's unique situation appears to be lacking. This article examines the literature around salutogenic and SOC theories and provides an overview of how a salutogenic assessment tool could be used in paramedic practice. Taking a multifactorial approach to determining health status and predicating patient capacity for adaptive coping may make health professionals better able to assist patients in overcoming health events and build health resilience to improve their future health outcomes.